Primary fibrosarcoma im small intestine of dog - Case report - Magalhâes, Geórgia Modé; Santilli, Juliana; Calazans, Sabryna Gouveia; Nishimura, Lilian Toshiko; De Amorim Cerejo, Sofia [UNESP]; Dias, Fernanda Gosuen Gonçalves (My University, 2015)
Intestinal neoplasms are uncommon in dogs, and among the most frequently diagnosed are smooth muscle, lymphomas and carcinomas. The fibro-sarcoma is extremely rare in the intestine of animals of this species therefore, little is known about the macroscopic and behavior of this tumor. Given this unusual intestinal disease in dogs, the present study aimed to report a case of intestinal fibrosarcoma in a poodle breed dog, 15 years old, with no apparent clinical signs. The mass was pedunculated, whitish and firm consistency. The diagnosis was made by histopathology. After four months of surgical excision, there was no recurrence and metastasis. We conclude that the intestinal fibro-sarcoma has low aggressiveness, are rare and can present macroscopic pedic-ulated.
Fibrossarcoma primário em intestino delgado de câo - Relato de caso
Keywords: Dogs; Fibrosarcoma; Intestinal neoplasms